Telomeres and telomerase: A dual role in hepatocarcinogenesis - Satyanarayana Ande; Michael P. Manns; K. Lenhard Rudolph (2004)
Telomere shortening limits the proliferative capacity of primary human cells and restrains the regenerative capacity of organ systems during chronic diseases and aging. Telomere shortening apparently has a dual role in tumor development and progression. On the one hand, it induces chromosomal instability and the initiation of cancer; on the other hand, tumor progression requires stabilization of telomeres. The predominant mechanism of telomere stabilization in tumor cells is the activation of the telomere-synthesizing enzyme telomerase. The potential use of telomerase activators for the treatment of regenerative disorders will ultimately depend on their effects on tumorigenesis. This review focuses on the role of telomere shortening and telomerase in carcinogenesis with a special focus on hepatocellular carcinoma. (Hepatology 2004;40:276-283.)